1982
DOI: 10.1161/01.cir.65.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma lipid and lipoprotein levels in men and women after a program of moderate exercise.

Abstract: Levels of high-density lipoprotein (HDL) cholesterol and other lipids and lipoproteins of 24 men and 37 women were measured before and after a 10-week exercise program. The program involved three sessions of aerobic exercise each week, with 15-20 minutes of activity at 70% of maximal heart rate. Men and women had significantly different lipid patterns in response to exercise, despite equivalent increases in maximal oxygen uptake. Men showed a 5.1% increase in HDL cholesterol, a 6% decrease in low-density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(44 citation statements)
references
References 42 publications
3
39
0
2
Order By: Relevance
“…For example, several investigators have described age-related changes in lipid and lipoprotein levels, including increases in low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and total cholesterol (TC), and decreases in high-density lipoprotein cholesterol (HDL-C) up to middle age. [1][2][3][4][5][6][7] Physical activity and moderate alcohol consumption are related to decreases in LDL-C and TC, and increases in HDL-C. [8][9][10] In women, the menopausal transition is strongly associated with increases in LDL-C and TC, and in some studies with changes in TG and HDL-C. 2,[11][12][13][14] The majority of these findings, however, are from analyses of cross-sectional data, or from data gathered in studies that had relatively short follow-up periods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Adiposity is an important influence on adult lipid and lipoprotein profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several investigators have described age-related changes in lipid and lipoprotein levels, including increases in low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and total cholesterol (TC), and decreases in high-density lipoprotein cholesterol (HDL-C) up to middle age. [1][2][3][4][5][6][7] Physical activity and moderate alcohol consumption are related to decreases in LDL-C and TC, and increases in HDL-C. [8][9][10] In women, the menopausal transition is strongly associated with increases in LDL-C and TC, and in some studies with changes in TG and HDL-C. 2,[11][12][13][14] The majority of these findings, however, are from analyses of cross-sectional data, or from data gathered in studies that had relatively short follow-up periods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Adiposity is an important influence on adult lipid and lipoprotein profiles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Physical activity and moderate alcohol consumption are related to decreases in LDL-C and TC, and increases in HDL-C. [8][9][10] In women, the menopausal transition is strongly associated with increases in LDL-C and TC, and in some studies with changes in TG and HDL-C. 2,[11][12][13][14] The majority of these findings, however, are from analyses of cross-sectional data, or from data gathered in studies that had relatively short follow-up periods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Adiposity is an important influence on adult lipid and lipoprotein profiles. [15][16][17][18][19][20][21] The body mass index (BMI) is often used as a proxy measure of adiposity and in adults BMI is positively related to LDL-C, TG and TC, and negatively related to HDL-C. 22 However, BMI is a composite of adipose and lean tissues, both of which can have distinct effects on lipid and lipoprotein levels.…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al 30) found decreases in serum TC, HDL-C, and LDL-C levels in trained subjects who performed at 70%-85% of their maximum heart rates for 4 weeks, which is different from the findings of the present study. In contrast, 3 months of moderate aerobic exercise did not improve BLLP levels in females 31) . The differences in BLLP levels due to exercise primarily depend on exercise intensity, duration, and frequency, as well as lifestyle factors such as diet, sex, smoking, and alcohol consumption 1,17,32,33) .…”
Section: Correlations Among Variablesmentioning
confidence: 62%
“…However, results from prospective surveys and intervention studies are equivocal. Five of eight exercise trials conducted among men [17] showed significant increases in HDL-C with exercise. Three of these trials evaluated the effect of exercise in women, but no significant differences were reported.…”
Section: Discussionmentioning
confidence: 98%